Recurrent hepatocellular carcinoma with osteoclast-like giant cells: a case report - Mone Tsukimoto; Kazushi Sugimoto; Ryuta Shigefuku; Ryosuke Sugimoto; Hiroto Yuasa; Katsunori Uchida; Norihiko Yamamoto (Journal of Medical Case Reports, 2022)
Abstract Background Hepatocellular carcinoma with osteoclast-like giant cells is very rare and has an extremely poor prognosis. Here, we report a case of hepatocellular carcinoma with osteoclast-like giant cells that had a relatively better prognosis. Case presentation A 70-year-old Japanese man with hepatitis B virus-related liver cirrhosis was admitted to our hospital for the treatment of recurrent hepatocellular carcinoma. At the age of 60 years, he was first diagnosed as having hepatocellular carcinoma in the right lobe (9 cm in diameter), and liver resection of segment 7/8 was performed. Histological findings showed well-differentiated hepatocellular carcinoma. Since then, imaging studies have been performed every 3 or 4 months. One year later, hepatocellular carcinoma recurred in the lateral segment, and radiofrequency ablation was performed. Nine years after the first presentation, hepatocellular carcinoma recurrences were detected in the caudate lobe and segment 5 by imaging studies. Surgical resection of the caudate lobe was performed, and ultrasonography-guided radiofrequency ablation was subsequently performed for the segment 5 tumor. The resected tumor was simple nodular, well-differentiated HCC; it measured 21 × 21 mm and contained many osteoclast-like giant cells. As neither vascular nor bile duct invasion was found, we believe that radical resection was achieved. Since then, the hepatocellular carcinoma has not recurred for over a year and a half. Conclusion Hepatocellular carcinoma with osteoclast-like giant cells is very rare and the prognosis is extremely poor, but early detection can lead to a better clinical course.